WAKTU DAN TEMPAT KEMUNCULAN HADIS: Suatu Diskursus Kesarjanaan - Aceng Abdul Kodir (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2021)
From the very beginning, Hadith came with inherent problems. At least, two aspects always accompany the study of the Prophet's Hadith, namely authenticity and authority. Authenticity has been a subject of study to challenge hadith scholars, from the past until now. The best achievement from study of Hadith authenticity is knowing and discovering the origins of Hadith, both in aspects of time and place. The authority aspect of hadith as a source of Islamic teachings was well resolved by al-Shafi'i (d. 204) until he received the title nasir al-sunnah. This article intends to introduce the latest trends in the study from origins of Hadith; first, regarding the time, when a hadith appears, second, regarding the place where a hadith was born. To produce a convincing formulation, the author uses the study of regional Hadith (regionalism). In conclusion, regional Hadith studies can answer not only when, but also where a hadith was born and became mainstream in a particular area.